SOSIALISASI PENTINGNYA ADMINISTRASI KEPENDUDUKAN KEPADA ANGGOTA PKK KELURAHAN SURABAYA KECAMATAN SUNGAI SERUT KOTA BENGKULU - Is Susanti; Muhammad Fauzan Aziman (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2025)
This community service activity aims to inform the public that population data is essential. Birth certificates, family cards, and identity cards (after the age of seventeen) are the three fundamental components that every Indonesian citizen must have. This data is crucial for the continuity of a country, as it directly impacts policymaking and the development of government programs. From birth, a person already requires population administration. In this service activity, we emphasized that beyond the creation of these documents, the archiving and maintenance of population administrative records must also be taken seriously. While the creation process is fully managed by the government, guidance is needed for archiving and maintaining these documents so that the public becomes more aware of the importance of complete population administration. Based on this rationale, we conducted a socialization session for all members of the PKK (Family Welfare Movement) in the Surabaya, Sungai Serut, Bengkulu. Surabaya is considered quite complex, consisting of a total of 29 neighborhood associations (RTs). The method we used in this community service was to conduct a socialization session while also highlighting the negative impacts of incomplete population administration. Through this session, it is hoped that the public will become more aware and concerned about their population documents, enabling Indonesia to carry out development more effectively as its citizens are well-identified. Keywords: Administration; Population; Policy; PKK; Bengkulu.